Mothering from the inside : research on motherhood and imprisonment - Lockwood, Kelly (Emerald Publishing Limited, 2020)
Based on empirical research, this edited collection brings attention to the experiences and perspectives of women who are 'mothering from the inside', along with those of their children, families and wider support networks. Exploring a range of distinct, yet interrelated, issues explicitly associated with maternal imprisonment, the collection is separated into two parts. Part I, 'From sentence to resettlement', explores sentencing, maintaining maternal contact, pregnancy and childbirth, and resettlement, whilst also attending to the lived experiences and needs of children with a mother in prison. Part II, 'From the margins to the centre', explores diverse perspectives in relation to mothering and imprisonment, highlighting the importance of understanding how factors such as age and mental health intersect with mothers' lived experiences of and responses to imprisonment. The perspectives of prison officers as mothers are also considered, along with international perspectives on mothering and imprisonment, identifying key issues of commonality and difference. Ultimately, the book highlights the challenges of and barriers to mothering and imprisonment, whilst also illustrating the adaptive strategies adopted in order to resist and/or survive the impact of maternal imprisonment. In doing so, the collection highlights crossdisciplinary themes to encourage debate in relation to issues in contemporary practice. The book is essential reading for scholars and students in the areas of criminology, sociology, social policy and law.